No one would do what the Lamberts have done : a novel - Hannah, Sophie, 1971- (Sourcebooks Landmark, 2026)
When a family is confronted with a serious accusation involving their dog, they are forced to make an extreme decision that upends their lives. As events escalate, the Lamberts leave behind their home and community, entering an uncertain and dangerous situation. This novel explores themes of loyalty, fear, and the lengths individuals may go to protect those they love.